Exploring Types of Language Learning Motivation among EFL Students: Insights from Rwandan High Schools - Ndayisenga, Jean d'Amour; Laos Mbato, Concilianus (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Motivation in language learning is a critical area of study since motivation greatly impacts second language acquisition. Socio-Educational Model theory explains motivation to learn a second language in two main types: integrative and instrumental motivation. Many studies have explored motivation in language learning, but such studies are deficient in the case of Rwandan EFL learners. This study analyses the motivational types that inspire students during learning and investigates the motivation factors for EFL learning. This descriptive study, which involves a class from a Rwandan high school of Groupe Scolaire Nyamirama, uses both a qualitative and quantitative design. The information was gathered using open-ended questionnaires and closed-ended questionnaires. The results indicated that instrumental and integrative motivation significantly influences students’ EFL learning process. However, it showed that instrumental motivation was major in EFL learning. Additionally, according to the data, twelve motivational factors were identified from students and ten from teachers regarding teaching strategies and teacher-student interactions, all which impact students during the learning process. However, because motivational variables and motivational types rely on context, it is recommended that a study on this topic be conducted in a different setting.